2022
DOI: 10.1021/acscatal.2c00684
|View full text |Cite
|
Sign up to set email alerts
|

Disordered, Sub-Nanometer Ru Structures on CeO2 are Highly Efficient and Selective Catalysts in Polymer Upcycling by Hydrogenolysis

Abstract: Nondegradable polyolefin plastics pose severe environmental threats and thus demand efficient upcycling technologies. In this work, we discovered that low-loading (≤0.25 wt %) Ru/CeO2 exhibits remarkable catalytic performance in the hydrogenolysis of polypropylene (PP), polyethylene (PE), and n-C16H34 that is superior to high-loading (≥0.5 wt %) Ru/CeO2. They possess high PP conversion efficiency (sevenfold increase over current literature reports), low selectivity toward undesired CH4, and good isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 50 publications
3
81
0
Order By: Relevance
“…The combined mass of the volatiles and DCM extract fractions as a percentage of the initial reactant polyolefin mass is taken as the percent conversion for a given polyolefin hydrogenolysis reaction. These analytical methods for handling polyolefin hydrogenolysis products are similar to those used in the recent polyolefin hydrogenolysis literature 12 , 14 , 28 .…”
Section: Resultsmentioning
confidence: 98%
“…The combined mass of the volatiles and DCM extract fractions as a percentage of the initial reactant polyolefin mass is taken as the percent conversion for a given polyolefin hydrogenolysis reaction. These analytical methods for handling polyolefin hydrogenolysis products are similar to those used in the recent polyolefin hydrogenolysis literature 12 , 14 , 28 .…”
Section: Resultsmentioning
confidence: 98%
“…10 Thus, to test the hypothesis, we impregnated Ni and Pt onto TiO2-A-SG (0.07 M/nm 2 ), both of which are inert for C−C bond cleavage, i.e., hydrogenolysis, under these conditions. 12,13,26 Figure 2a shows that both Ni and Pt convert PP on TiO2-A-SG more efficiently than Ru, yielding similar product distribution (Figures 2d and S3b): no CH4, much more C4-5 than C2-3, narrow liquid distribution around C10, and yellow-colored products (Figure S2f). In addition, the TiO2-A-SG support alone, without any metal, can convert ~5% PP (Figure 2a), also with similar product distribution (Figure S3c).…”
Section: Bifunctional Ru/tio2-a-sg Catalyzing Both Hydrocracking and ...mentioning
confidence: 98%
“…For hydrogenolysis, most studies used catalysts with high noble metal (Ru or Pt) content, 12,13,[15][16][17][18][19][20][21][22][23][24][25] and the selectivity needs to be steered away from low-valued gas alkanes, especially CH4, to high-valued liquid alkanes. We have shown that disordered Ru clusters have better activity and selectivity in the reaction than rigid particles, 26 but the structure-function relationship needs further understanding for the rational design of active sites. For hydrocracking, most studies used expensive, scarce Pt as the metal, [27][28][29][30][31][32][33][34] and zeolites as the acidic support, [30][31][32][33][34][35] the microporous structure of which creates difficulty for the diffusion of long-chain polymers and thus limits active site accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages and disadvantages of these technologies are summarized in Table . In the available chemical approaches, the well-developed catalysts, processes, and infrastructures in traditional industries can readily be adopted for the transformation of waste plastic into valuable products. ,,,,,,, In particular, there are pilot- or industrial-scale processes for recycling monomers from postconsumer plastics . However, many chemical methods still suffer from harsh reaction conditions (e.g., high temperature and pressure), limiting their application in an environmentally benign fashion.…”
Section: Outlook and Perspectivementioning
confidence: 99%